A escrita da história entre dois mundos: uma análise da produção de Alice Piffer Canabrava (1935-1961) - Erbereli Júnior, Otávio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
On this dissertation, we pervade the historiographical production of Alice Piffer Canabrava (1911-2003) from the major concerns of History of Historiography. We privilege the period comprehended between 1935, the year of Canabrava‘s join in the Geography and History‘s graduation on the Faculty of Philosophy, Sciences and Letters (FFCL) of São Paulo University (USP), and, 1961, the foundation year of the Higher Education Professores on History Association (APUH), in the FFCL of Marília-SP. We have tried to comprehend Alice Piffer Canabrava‘s Writing History trough the notion of Michel De Certeau‘s historiographical operation. The Canabrava‘s formative place, which is, the several Chairs‘ classes of the V sub section on Geography and History of II Sciences section of USP‘s FFCL during the period in which she was a student, between 1935 and 1937, helped us to comprehend her choices and historiographical practices, like her notions of History and Document, as well as a long term mobilization knowledge: the vidalian Geography. We also have demarcated the 1946‘s competition for the American Civilization History as the focal point of Alice Canabrava‘s intellectual trajectory, once after having been deprecated on this event, settled down on the Faculty of Administration and Economics Sciences, founded in the same year. This new place provided her aids to incorporate Economics on her historiographical production. We expect that this work can contribute to the comprehension of a special moment the History of Historiography: the constitution of university historiographical production

Nesta dissertação, perpassamos a produção historiográfica de Alice Piffer Canabrava (1911-2003) a partir das principais preocupações da História da Historiografia. Privilegiamos o período compreendido entre 1935, ano de ingresso de Canabrava no curso de Geografia e História da Faculdade de Filosofia, Ciências e Letras (FFCL) da Universidade de São Paulo (USP), e 1961, ano de fundação da Associação dos Professores de História do Ensino Superior (APUH), atual ANPUH, na FFCL de Marília-SP, da qual essa historiadora foi uma de suas fundadoras. Procuramos compreender a Escrita da História de Alice Piffer Canabrava através da noção de operação historiográfica formulada pelo historiador-jesuíta Michel De Certeau. O lugar formativo de Canabrava, qual seja, os cursos das várias Cadeiras da V subseção de Geografia e História da II seção de Ciências da FFCL da USP durante o período em que foi aluna da graduação, entre 1935 e 1937, nos auxiliou a compreender várias de suas escolhas e práticas historiográficas, como suas noções de História e Documento, bem como um conhecimento de larga mobilização: a Geografia de matriz vidaliana. Também demarcamos o concurso para a Cadeira de História da Civilização Americana de 1946 como ponto fulcral da trajetória intelectual de Alice Canabrava, uma vez que após ser preterida neste certame, estabeleceu-se na Faculdade de Ciências Econômicas e Administrativas (FCEA) da USP, fundada no mesmo ano. Esse novo lugar lhe forneceu os subsídios para incorporar a Ciência Econômica em sua produção historiográfica. Esperamos que este trabalho possa contribuir para a compreensão de um momento ímpar da História da Historiografia brasileira: da constituição da produção historiográfica no âmbito universitário
Keywords: Canabrava, A. P Alice Piffer 1911; Historiografia; Historia - Metodologia; Historia - Filosofia; History; Brasil - Historiografia